MICROBIOLOGICAL ANALYSIS AND SANITARY AND HYGIENIC CONTROL OF RAW MILK - Прилипко, Татьяна; Букалова, Наталья; Богатко, Надежда (SWorldJournal, 2022)
Microbiological analysis and sanitary and hygienic control of raw milk. According to the results of the study of raw whole cow’s milk presented in the article, its contamination was established not only by micrococci, psychrophilic microorganisms of the g